Associação entre osteoporose e osteoartrite: estudo clínico e densitométrico - MARTINS, Adriana Edelves Trindade (2022)
Osteoporosis (OP) and osteoarthritis (OA) are, both, osseo metabolism illnesses. The first one is characterized for the reduction of the óssea mineral density and the second one is characterized for the increase of óssea mineral density. Would they be mutually exclusive each other ? In order to answer this complex and intriguer question, this study looked to determine the number of cases of osteoporosis in patients with generalized OA and located on the knees OA. Besides, it made a comparison research of the ossea mineral density of these patients. For this purpose, it were selected 24 patients with osteoarthritis, as so: 12 with generalized osteoarthritis (group 1) and 12 with knees located osteoarthritis (group 2). All 24 were female, maximum 65 years old and after the menopaused. The evaluation of the osseo metabolism was made through anamnese, physical examination, hands and knees x-ray, ossea densitometria and laboratory examinations. Of the 24 patients with OA, nine (37.5%) had the OP diagnosis, and of these, eight (88.9%) belonged to the generalized group of OA and only one (11.1%) to the group of knees located OA. This data is relevant on a statistical view, since it presented p = 0,0094 (p < 0,05). So, based on the data collected, this paper concludes that osteoporosis and osteoarthritis are not mutually exclusive each other and that the amount of the OP appearance varies according to where the OA is located.